Formal and informal methods in philosophy - Będkowski, Marcin, (Poznań Studies in the Philosophy of the Sciences and the Humanities;, 2020)
"This book examines the tension between formal and informal methods in philosophy. The rise of analytic philosophy was accompanied by the development of formal logic and many successful applications of formal methods. But analytical philosophy does not rely on formal methods alone. Elements of broadly understood informal logic and logical semiotics, procedures used in natural sciences and humanities, and various kinds of intuition also belong to the philosopher's toolkit. Papers gathered in the book concern the opposition formality-informality as well as other pairs, such as methodology versus metaphilosophy, interdisciplinarity versus intradisciplinarity, and methodological uniformity versus diversity of sciences. Problems of the nature of logic and the explanatory role of mathematical theories are also discussed".